2022
DOI: 10.1016/j.foodchem.2021.130589
|View full text |Cite
|
Sign up to set email alerts
|

Computational modeling predicts potential effects of the herbal infusion “horchata” against COVID-19

Abstract: Bioactive plant-derived molecules have emerged as therapeutic alternatives in the fight against the COVID-19 pandemic. In this investigation, principal bioactive compounds of the herbal infusion “horchata” from Ecuador were studied as potential novel inhibitors of the SARS-CoV-2 virus. The chemical composition of horchata was determined through a HPLC-DAD/ESI-MS n and GC–MS analysis while the inhibitory potential of the compounds on SARS-CoV-2 was determined by a computational predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…The computational methodology used for target prediction consisted in the consensus of different models of target–compound interaction predictions previously applied in other investigations [ 66 , 67 ]. Briefly, all the possible target proteins of compound 9 in Homo sapiens were predicted using the following algorithms: MolTarPred [ 68 ], Swisstarget Prediction [ 69 ], Targetnet Scbdd [ 70 ], Targetnet Scbdd Ensemble [ 70 ], RF QSAR [ 71 ], and PPB2 [ 72 ].…”
Section: Methodsmentioning
confidence: 99%
“…The computational methodology used for target prediction consisted in the consensus of different models of target–compound interaction predictions previously applied in other investigations [ 66 , 67 ]. Briefly, all the possible target proteins of compound 9 in Homo sapiens were predicted using the following algorithms: MolTarPred [ 68 ], Swisstarget Prediction [ 69 ], Targetnet Scbdd [ 70 ], Targetnet Scbdd Ensemble [ 70 ], RF QSAR [ 71 ], and PPB2 [ 72 ].…”
Section: Methodsmentioning
confidence: 99%
“…The repurposing potential of 34 bioactive terpenes and their derivatives to Mpro and PLpro was also predicted by docking and MM/PBSA calculations . Other MM/PB­(GB)­SA-based drug repurposing works considering two or more targets include studies in the literature. …”
Section: Methods and Approachesmentioning
confidence: 99%
“…The horchata mixture exhibits anti-inflammatory, analgesic, diuretic, and antioxidant activity [ 11 , 12 , 13 , 14 ]. Our group identified that the hydroalcoholic extract (methanol-water, 80:20 v / v ) of the horchata mixture contains a wide range of phenolic compounds, the most prominent being the flavones, flavonols (e.g., quercetin glycosides and apigenin glycosides), and chlorogenic acids (such as caffeoylquinic and dicaffeoylquinic acids) [ 12 ]; compounds found in different medicinal plants and with known antimicrobial properties [ 1 , 2 , 15 ].…”
Section: Introductionmentioning
confidence: 99%